Should encountering atypia of undetermined significance / follicular lesion of undetermined significance after thyroid biopsy lead to the operation? - Çelebi, Bilgin; Taşdelen, Halil Afşin; Kurnaz, Eray (The European Research Journal, 2023)
Objectives: Nodular goiter is the most common disease of the thyroid gland. Thyroid nodules are malignant in 3-5% cases. To determine the incidence of malignancy in patients defined as atypia of undetermined significance (AUS) or follicular lesion of undetermined significance (FLUS) as a result of fine needle aspiration biopsy (FNAB) and evaluate the clinical, biochemical and sonographic features as possible predictors of malignancy. Methods: Patients who had undergone at least one FNAB and diagnosed as AUS/FLUS from January 2011 to December 2015 were included in the study. Age, gender, benign disease, thyroid stimulating hormone (TSH) level, size, localization, number, time of FNAB, ultrasonography (USG) characteristics, follow-up data on repeated FNAB results and, if surgical excision was performed, final pathological results were analyzed. Results: A total of 5181 thyroid nodules were biopsied in 4089 patients, and the biopsy specimen taken from 611 nodules was diagnosed histopathologically as AUS/FLUS (11.79%). After FNAB, 167 of 611 patients diagnosed with AUS/FLUS were operated. While 65.9% (n = 110) of 167 patients who underwent surgery were made a benign diagnosis; malign diagnosis was made to 34.1% (n = 57). Conclusions: The rate of malignancy in surgically confirmed nodules was 34.1% in this study, which is higher than the Bethesda classification. Due to the high malignancy rate which determined in cytologically diagnosed AUS/FLUS, we think that the repeat decision of the FNAB should be reconsidered and the surgical plan after the first FNAB should be considered more seriously.